How Arsenic, an Inorganic Pollutant, is Involved in the Physiology of Biomolecular Condensates in the Cell - Udagawa, Osamu; Hirano, Seishiro (Frontiers in Environmental Chemistry, 2022)
The existence of membrane-less organelles in the cells has been known for a relatively long time. Of the membrane-less organelles, stress granules, processing bodies, and PML-NBs have been intensively investigated in relation to arsenic. The membrane-less organelles, which concentrate biomolecules (proteins, nucleic acids), have recently been shown to self-organize by means of phase separation/transition. These biomolecular condensates (membrane-less organelles) can provide local enhancement of the efficiency of specific reactions. The biomolecular condensates have attracted dramatic attention over the last decade because highly organized biochemical complexes in the cell have long been understood by the membrane-dependent compartmentalization. In this mini review, we highlight the initiation of phase separation for each biomolecular condensate in which arsenic could be involved. We further reflect on the adequacy of the arsenic-dependent ROS levels for the formation of biomolecular condensates. These perspectives led us to re-evaluate the biological action of arsenic from a biophysical and bio-rheological point of view.